Sense of coherence promotion and occupational and family stress mitigation may improve heart health behaviors in middle-aged working women: a structural equation modelling approach - Moon, Ji Hyun; Seo, Eunhye (Frontiers in Public Health, 2024)
Aims This study aimed to construct a model that describes heart health behaviors in middle-aged working women and verify the goodness-of-fit of the model based on Salutogenesis. Methods and results This study adopted a cross-sectional design. Participants were 330 middle-aged working women in South Korea. Data were analyzed using structural equation modelling with Sobel’s Z test. In the multiple mediation model, stress coping strategy (β = 0.26; p < 0.001), social support (β = 0.41; p < 0.001), and health self-efficacy (β = 0.36; p < 0.001) had significant direct effects on sense of coherence (SOC). SOC had a significant direct effect on occupational (β = −0.72; p < 0.001) and family stress (β = −0.76; p < 0.001). Additionally, SOC (β = 0.67; p < 0.001), occupational stress (β = −0.46; p < 0.001), and family stress (β = −0.28; p < 0.001) had significant direct effects on heart health behaviors. Moreover, SOC had a significantly partial mediating effect on heart health behaviors through occupational stress (Z = 3.17; p = 0.002) and family stress (Z = 2.26; p = 0.024). Conclusion Occupational and family stress mediated the relationship between SOC and heart health behaviors in middle-aged working women. Clinical evidence Interventions that mitigate occupational and family stress may improve heart health behaviors among middle-aged working women.